2007
DOI: 10.1094/phyto-97-4-0429
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Modulation of Gene Expression in Tomato by Trichoderma hamatum 382

Abstract: A light sphagnum peat mix inoculated with Trichoderma hamatum 382 consistently provided a significant (P = 0.05) degree of protection against bacterial spot of tomato and its pathogen Xanthomonas euvesicatoria 110c compared with the control peat mix, even though this biocontrol agent did not colonize aboveground plant parts. To gain insight into the mechanism by which T. hamatum 382 induced resistance in tomato, high-density oligonucleotide microarrays were used to determine its effect on the expression patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
129
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(142 citation statements)
references
References 39 publications
7
129
0
6
Order By: Relevance
“…In the Trichoderma ‐plant interaction, it has been shown that the fungus re‐programmes the plant's transcriptome, proteome and metabolome leading to enhancement of the plant's ability to tolerate different types of stresses (Alfano et al ., 2007; Shoresh et al ., 2010). …”
Section: Discussionmentioning
confidence: 99%
“…In the Trichoderma ‐plant interaction, it has been shown that the fungus re‐programmes the plant's transcriptome, proteome and metabolome leading to enhancement of the plant's ability to tolerate different types of stresses (Alfano et al ., 2007; Shoresh et al ., 2010). …”
Section: Discussionmentioning
confidence: 99%
“…(Carpenter et al, 2005;Liu & Yang, 2005;Scherm et al, 2009;Vizcaíno et al, 2006Vizcaíno et al, , 2007. Several researchers have explored the responses of plants to the presence of a root-colonizing Trichoderma strain (Alfano et al, 2007;Marra et al, 2006;Segarra et al, 2007;Shoresh & Harman, 2008), but the fungal component of this association has been less studied. Macroarray analyses have been applied to study the gene expression of four species of Trichoderma during their interaction with cacao seedlings (Bailey et al, 2006), and of Trichoderma harzianum during the early colonization of tomato roots (Chacó n et al, 2007), although one limitation to such studies has been the low number of genes tested.…”
Section: Introductionmentioning
confidence: 99%
“…Many species of Trichoderma are closely associated with plant roots and specific strains may form endophytic associations with their plant host (Bailey et al, 2006, Evans et al, 2003, Hoyos-Carvajal et al, 2009bManesh et al, 2006, Sette et al, 2006, Viterbo & Chet 2006, Yedidia et al, 2000. As endophytes they are particularly effective biological control agents of fungi in the rhizosphere, producing antimicrobials, activating plant defence mechanisms, and stimulating plant growth and vigour by solubilizing minerals and providing other nutrients and growth regulating compounds (Alfano et al, 2007;Altomare et al 1999;Sharon et al, 2001;Vinale et al, 2006, Woo et al, 2006, Yedidia et al, 2000. The multiple roles of Trichoderma in biotrophic decomposition, parasitism and endophytic associations are of particular importance to the sustainability of agricultural and natural ecosystems (Harman et al 2004).…”
Section: Introductionmentioning
confidence: 99%